(untitled) (Experimental biology, 2020)
Legionellosis is a sapronous acute infectious disease, with a mortality rate of about 10% in the pulmonary form, caused by various types of microorganisms belonging to the genus Legionella. According to current data, about 90% of legionellosis is associated with the species L. pneumophila. The main habitat of Legionella is abiotic environmental objects. Legionella in the majority of cases is sown from respiratory therapy equipment, air conditioning fluids, home and industrial cooling systems, shower and boiler installations. Observations have shown that the incidence of legionellosis in travelers is slightly higher than in people who do not change their location. The purpose of this work was to study the contamination of L. pneumophila in artificial water systems of four hotels in Almaty. Flushes from various objects of water systems and water samples were selected as the material for analysis. Bacteriological studies of the samples did not yield positive results. A PCR study of 30 samples revealed 4 positive samples in one of the hotels. It was found that the water temperature in the hot water system does not exceed 40-60°C all year round. The optimal temperature in water use systems for bacterial growth is 25-60°C. Key words: Legionellosis, Legionella, PCR, gene sections, bacteriology, molecular genetic method.